Antioncogenic Effects of Transient Receptor Potential Vanilloid 1 in the Progression of Transitional Urothelial Cancer of Human Bladder. (6th February 2012) - Santoni, Giorgio; Caprodossi, Sara; Farfariello, Valerio; Liberati, Sonia; Gismondi, Angela; Amantini, Consuelo
Abstract : The progression of normal cells to a tumorigenic and metastatic state involves the accumulation of mutations in multiple key signaling proteins, encoded by oncogenes and tumor suppressor genes. Recently, members of the TRP channel family have been included in the oncogenic and tumor suppressor protein family. TRPM1, TRPM8, and TRPV6 are considered to be tumor suppressors and oncogenes in localized melanoma and prostate cancer, respectively. Herein, we focus our attention on the antioncogenic properties of TRPV1. Changes in TRPV1 expression occur during the development of transitional cell carcinoma (TCC) of human bladder. A progressive decrease in TRPV1 expression as the TCC stage increases triggers the development of a more aggressive gene phenotype and invasiveness. Finally, downregulation of TRPV1 represents a negative prognostic factor in TCC patients. The knowledge of the mechanism controlling TRPV1 expression might improve the diagnosis and new therapeutic strategies in bladder cancer.